Suboptimal Biological Sampling as a Probable Cause of False-Negative COVID-19 Diagnostic Test Results. (28th June 2020) - Kinloch, Natalie N; Ritchie, Gordon; Brumme, Chanson J; Dong, Winnie; Dong, Weiyan; Lawson, Tanya; Jones, R Brad; Montaner, Julio S G; Leung, Victor; Romney, Marc G; Stefanovic, Aleksandra; Matic, Nancy; et al.
Abstract: False-negative severe acute respiratory syndrome coronavirus 2 test results can negatively impact the clinical and public health response to coronavirus disease 2019 (COVID-19). We used droplet digital polymerase chain reaction (ddPCR) to demonstrate that human DNA levels, a stable molecular marker of sampling quality, were significantly lower in samples from 40 confirmed or suspected COVID-19 cases that yielded negative diagnostic test results (ie, suspected false-negative test results) compared with a representative pool of 87 specimens submitted for COVID-19 testing. Our results support suboptimal biological sampling as a contributor to false-negative COVID-19 test results and underscore the importance of proper training and technique in the collection of nasopharyngeal specimens. Abstract : Improper nasopharyngeal swab collection could compromise COVID-19 diagnosis. In support of this, suspected false-negative specimens from confirmed or suspected COVID-19 cases contained less human DNA (a molecular marker of sampling quality) compared with a representative specimen pool submitted for testing.